Changes in the Physical and Functional Status of Physiotherapy Students During Their Studies - Laura Žlibinaitė; Laura Baumann; Kristina Vyrtosu; Karolis Stukonis (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. During their studies in physiotherapy, students acquire theoretical and practical knowledge about the benefits of physical activity, health parameters and disease prevention, as well as try out different forms of physical activity during practical sessions. However, there is a lack of data on the impact of the knowledge acquired in the course on students’ physical condition and on the changes in students’ physical and functional status.